An Exploratory Study of Environmental Stress in Four High Violent Crime Cities: What Sets Them Apart?. (October 2022) - Smith, Sven; Ferguson, Christopher J.; Henderson, Howard
Understanding the social contexts of violent crime remains controversial in the literature. In the current study, we examine common social contexts in four cities (Houston, TX, Baltimore, MD, Jackson, MS, Wilmington, DE). Data were examined in two studies. In the first, each city was compared to national county-level data on health outcomes. In the second, communities within the four cities were examined for correlates of crime. Results suggest that some common social contexts emerge: high STD rates, air pollution, single-parent homes, insufficient food resources and sleep, residential segregation, housing cost burdens, comparatively few older adults and comparatively more females, were common among the four high-violence cities. By contrast, all four cities unexpectedly had uncommonly low suicide rates compared to the national average. At the community level, unemployment, community stress, median household income, and population density all correlated with criminal outcomes. High-violence cities tended to have higher proportions of Black residents, however community level evaluations suggested that class-related issues, not race per se, was correlated with violent crime.